Working Dogs: Form and Function, 2nd Edition - Otto, Cynthia M.; Wilsson, Erik; Cobb, Mia (Frontiers Media SA, 2020)
Dogs partner with humans in a wide array of work-related disciplines. As detectors, guides, guardians, stock herders, assistants and professional canine athletes, there is demand for more scientific knowledge to enhance the performance and success of human and working dog partnerships. This topic encompasses a holistic approach to the science of working dog performance. The ability of a dog to complete tasks depends on their physical and behavioral traits; their ability to exert themselves at various demanding tasks requires both physical and behavioral stamina, agility, and resilience. The influence and interactions of genetics, health, environment and training are areas that can provide new insight to improve performance in current dogs and future generations. The human impact on the success of the working dog team encompasses the human's physical, psychological and analytic perspectives, and the intersection of human and canine interspecies communication.